PENGEMBANGAN MOBILE ROBOT MULTIPLATFORM “ATMAROBO” SEBAGAI SARANA PENINGKATAN MINAT REMAJA DI BIDANG ROBOTIKA - Evans Karlin; Nova Eka Budiyanta; Melisa Mulyadi; Harlianto Tanudjaja (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2019)
This study aims to develop an attractive multiplatform learning robot and supported by a programming system that is easily understood by adolescents. Learning robots developed are wheeled educational robots that can be controlled manually using a controller (manual transporter) and automatically using sensors (line follower and automatic avoider). As data processing on the robot, two Arduino Nano are used with the help of Arduino IDE software, and for sending data, serial communication between Arduino Nano is used. The sensors used in this robot are light based sensors for line follower and ultrasonic for automatic avoiders. In addition, there is a separate controller from the robot in the form of the MIT APP Inventor program installed on a smartphone device and connected to the Bluetooth module on the robot for manual transporter. From the test results, the robot runs accurately following the black or white lines and successfully moves items, for automatic avoiders the robot can detect walls and follow the grooves of the wall with an angle of 90 degrees, while for manual transporter robots can be controlled using a controller application on an Android-based smartphone developed with MIT APP Inventor.